2006
DOI: 10.1182/blood-2005-11-4743
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial lipopolysaccharide fever is initiated via Toll-like receptor 4 on hematopoietic cells

Abstract: Lipopolysaccharide (LPS),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 20 publications
6
57
0
Order By: Relevance
“…By binding to and activating TLR-4 located on the fenestrated capillaries of the circumventricular organ in the blood brain barrier, they lead to release of prostaglandin E2 (PGE2) from the arachidonic acid pathway in cytoplasmic membranes [22][23][24]. Prostaglandin E2 is small molecule that easily diffuses across the blood brain barrier, binds to specific PGE2 receptors (EP3 receptor) in the preoptic area and then activates thermal neurons in the anterior hypothalamus to a higher thermal balance point [2,[22][23][24]. It is unclear whether microbial products also lead to elevation of the thermal balance point by gaining direct access to the brain through disruption of the BBS.…”
Section: The Humoral Pathwaymentioning
confidence: 99%
“…By binding to and activating TLR-4 located on the fenestrated capillaries of the circumventricular organ in the blood brain barrier, they lead to release of prostaglandin E2 (PGE2) from the arachidonic acid pathway in cytoplasmic membranes [22][23][24]. Prostaglandin E2 is small molecule that easily diffuses across the blood brain barrier, binds to specific PGE2 receptors (EP3 receptor) in the preoptic area and then activates thermal neurons in the anterior hypothalamus to a higher thermal balance point [2,[22][23][24]. It is unclear whether microbial products also lead to elevation of the thermal balance point by gaining direct access to the brain through disruption of the BBS.…”
Section: The Humoral Pathwaymentioning
confidence: 99%
“…These findings suggest that hematopoietically derived IL-6 of peripheral origin may play a role in generating the second phase of LPS induced fever. Previous work has suggested that the LPS recognition molecule Toll like receptor 4 (TLR4) on immune cells plays a critical role at the onset of the initial phase of fever, and that the later phases of fever are dependent in a redundant way on TLR4 on both hematopoietic and non-hematopoietic cells (Steiner et al, 2006). While those finding seem to indicate that signaling molecules, such as cytokines, released from immune cells initiates fever, they are in disagreement with the finding that the initiation of the febrile response elicited by intravenously administrated LPS precedes the appearance of IL-6 and other cytokines in the blood stream (Cartmell et al, 2000;Givalois et al, 1994;Roth et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The same strategy has been used by others to investigate the contribution to the sickness syndrome of hematopoietic vs. non-hematopoietic expression of TLR4 (Chakravarty and Herkenham, 2005;Steiner et al, 2006a), MyD88 (Gosselin and Rivest, 2008;Ruud et al, 2013b), and IL-1R1 (Matsuwaki et al, 2014).…”
Section: Mice Strainsmentioning
confidence: 99%